2022
DOI: 10.1186/s12884-022-04792-y
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section in Uruguay from 2008 to 2018: country analysis based on the Robson classification. An observational study

Abstract: Background The use of caesarean section has steadily increased, with Latin America being the region with the highest rates. Multiple factors account for that increase and the Robson classification is appropriate to compare determinants at the clinical level for caesarean section rates over time. The purpose of this study is to describe the evolution of caesarean section rates by Robson groups in Uruguay from 2008 to 2018 using a country level database. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
1
Order By: Relevance
“…A Uruguayan study, also using routine information gathered with SIP, found an overall CSR of 43.1%. In that study, Group 5 had the largest size and was the major contributor to overall CSR (30.6%) [ 14 ]. Another Mexican study found an overall CSR ranging from 53.5 to 48.7% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Uruguayan study, also using routine information gathered with SIP, found an overall CSR of 43.1%. In that study, Group 5 had the largest size and was the major contributor to overall CSR (30.6%) [ 14 ]. Another Mexican study found an overall CSR ranging from 53.5 to 48.7% [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…A nivel mundial la situación no es mucho más alentadora, comparando con los datos de Uruguay el porcentaje de cesáreas fue de un 46.3% en 2014, siendo más alto en Epriv 9,10 . En India entre los años 2005 y 2016 el porcentaje de cesáreas en Epriv aumentó del 27.9 al 40.9%, mientras que en los Epub disminuyó del 15.2 al 11.9% 11 .…”
Section: Discussionunclassified
“…4 Multiple factors account for that increase and the Robson classification is appropriate to compare determinants at the clinical level for caesarean section rates over time. 5 To safely reduce the increasing prevalence of CDs, the World Health Organization (WHO) recommended the Robson classification as a tool for monitoring and auditing CD rates in 2016. 6 The classification uses 6 basic obstetrical variables (parity, previous CD, onset of labour, gestational DOI: https://dx.doi.org/10.18203/2320-1770.ijrcog20230817 Department of Obstetrics and Gynecology, Mamata Medical College, Khammam, Telangana, India age, number of fetuses, fetal lie, and presentation) to classify each woman into 1 of 10 groups.…”
Section: Introductionmentioning
confidence: 99%